Longitudinal time-domain optic coherence study of retinal nerve fiber layer in IFNβ-treated and untreated multiple sclerosis patients - PUL, REFIK (Exp Ther Med, 2016)
Quantification of the retinal nerve fiber layer (RNFL) by optical coherence tomography (OCT) has been proposed to provide an indirect measure for retinal axonal loss. The aim of the present study was to determine whether interferon beta (IFNβ) treatment impedes retinal axonal loss in multiple sclerosis (MS) patients. A total of 48 patients with MS (24 IFNβ-1b-treated and 24 untreated subjects) and 12 healthy controls were enrolled in a prospective longitudinal OCT study. OCT measurements were performed for both eyes of each subject at baseline, and at 3-, 6-, and 12-month follow-up examinations using a time-domain OCT. At each visit, we additionally recorded full-field visual evoked potential (VEP) responses and performed the paced auditory serial addition test (PASAT), in addition to expanded disability status scale (EDSS) scoring. Generalized estimation equation (GEE) was used to account for repeated measurements and paired-data. The model-based approach predicted a monthly reduction in the RNFL thickness by 0.19 µm in the eyes of the MS subjects. The reduction was estimated to be 0.17 µm in case of IFNβ-treatment and 0.16 µm in case of no treatment. Treatment duration and group allocation were not significantly associated with the RNFL thickness. Inclusion of further longitudinal data (EDSS, two and three second PASAT) in each of our models did not result in any significant association. In summary, over a period of one year no significant association between IFNβ-1b treatment and RNFL thinning was identified in patients with MS.